Corporate value, price and dividend policy: A case study of U.S. listed firms - Boďa, Martin; Jerabek, Radoslav (John Wiley & Sons Ltd., 2024)
Focussed upon the U.S. stock market, the paper investigates the role of dividend policy, its level and (in)stability in generation of relative corporate value and relative stock price. Whilst relative corporate value is proxied by Tobin's q and relative stock price is operationalised by the four most frequent multiples (P/E, P/B, P/S and P/FCF), the dividend policy is represented by three popular metrics measuring the propensity to pay dividends. Controlling for operating and macroeconomic conditions, panel data techniques in a simultaneous equations framework are employed to 115,837 quarterly observations for 1466 firms represented in the S&P 1500 Composite Index over the period 1989-2022. The findings reveal that dividend policy matters, albeit the response of Tobin's and multiples to dividend policy is asymmetric. In particular, corporate value of U.S. firms is found to increase with per-share dividend amounts but decreases relative to the dividend payout ratio and yield. The established empirical evidence reaffirms claims against dividend neutrality and is useful in developing pre-selection investing strategies that relate practices in dividend policy to fundamental screening based on multiples.
Hodnota, cena a dividendová politika společnosti: případová studie společností kotovaných v USA
Keywords: unit-root tests; disappearing dividends; payout policy; panel-data; behavior; determinants; earnings; growth; ratios; testy na jednotkový kořen; mizející dividendy; výplatní politika; panel-data; chování; determinanty; zisk; růst; poměry